Performing the Other: Gamelan Parakan Salak dan Eksotisasi Identitas dalam Pertunjukan Etnik di Chicago - Icuh Komala; Asep Nugraha (Paraguna, 2025)
Since its first appearance at the 1893 World’s Columbian Exposition in Chicago, the Parakan Salak gamelan has undergone a shift from a living cultural practice to an object of exotic display embedded in colonial and multicultural narratives. This study investigates how the gamelan is represented in ethnic performance contexts in Chicago and how these representations reflect dynamics of power, exoticism, and identity negotiation. Employing a qualitative approach, this research integrates historical-contextual analysis, qualitative content analysis, and comparative analysis between formal institutions (museums, universities) and community-based performance spaces. Findings reveal that the gamelan is often framed as a token of cultural diversity—visually captivating yet removed from its original social and ritual meanings. Simultaneously, Indonesian diaspora communities have reclaimed the gamelan as a medium of expression and cultural agency, navigating tensions between authenticity and adaptation through performative strategies. This study contributes to critical discourse on the representation of non-Western cultures in diasporic and institutional settings, highlighting the need to reposition traditional arts not only as heritage but as dynamic spaces for negotiating identity, history, and cultural politics in a postcolonial and globalized world.